Automatic detection and correction of computational errors in programs - Maine, Paul A. D. de; Maine, Margaret M. de (Zielona Góra: Uniwersytet Zielonogórski)
Two different kinds of methods that are frequently used to evaluate functions are: Regression (for single-valued parameters) and Iteration (for multi-valued parameters). Comprehensive tests have established that both regression and iteration methods can yield unexpected false answers because their criteria are , necessary but not sufficient conditions. Working algorithms that automatically detect and correct computational errors are described.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka